Naming in Noise: The Contribution of Orthographic Knowledge to Speech Repetition - Pattamadilok, Chotiga; Morais, José J.; Kolinsky, Regine (Frontiers in Psychology, 2011)
While the influence of orthographic knowledge on lexical and postlexical speech processing tasks has been consistently observed, it is not the case in tasks that can be performed at the prelexical level. The present study re-examined the orthographic consistency effect in such a task, namely in shadowing. Comparing the situation where the acoustic signal was clearly presented to the situation where it was embedded in noise, we observed that the orthographic effect was restricted to the latter situation and only to high-frequency words. This finding supports the lexical account of the orthographic effects in speech recognition tasks and illustrates the ability of the cognitive system to adjust itself as a function of task difficulty by resorting to the appropriate processing mechanism and information in order to maintain a good level of performance.